Determinants of workplace incivility and violence faced by female doctors in medical institutions - Nasir, Mehreen; Iram Manzoor; Aleem Ullah Qureshi; Ghulam Rasool; Ayesha Anwar (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the frequency of workplace gender-based violence and incivility faced by female doctors. Method: The analytical, cross-sectional study was conducted from June 10 to August 31, 2023, in Lahore, Pakistan, and comprised female doctors working in 1 public and 1 private medical institution in Lahore. Data was collected using a questionnaire. Workplace incivility and various demographic factors were compared. Data was analysed using SPSS 21. Results: Of the 200 subjects, 138(69%) were from the private sector and 62(31%) were from the public sector. The majority was aged <30 years 95(47.5%). Some form of workplace violence was faced by 86(43%) doctors; psychological violence by 58(29%), verbal 56(28%), digital harassment 11(5.5%) and physical violence 2(1%). Supervisor incivility was faced by 94(47%) respondents, while 87(43.5%) faced co-worker incivility over the preceding year. Supervisor incivility was significantly higher in private institutions and those having income less than Rs100,000 per month (p<0.05). Conclusion: Workplace gender-based violence and incivility faced by working female doctors was found to be high. The most common forms faced were psychological and verbal violence. Supervisor incivility faced by female doctors at workplace was significantly higher in private institutions and those having monthly income less than Rs100,000. Key Words: Workplace incivility, Gender-based violence, Medical Institutions.